Le difficili relazioni tra Russia e Giappone - DE PALMA, Daniela (Franco Angeli, 2012)
Despite the passage of nearly 70 years since the end of World War II, between Russia and Japan have not yet signed a peace treaty, because of the difficult resolution of the dispute over the northern territories, hoppo ryōdo (ie the whole of the Kuril archipelago, the tiny group Habomai, Shikotan island and the southern part of the island of Sakhalin), that the Soviet Union occupied between 9 August and September 1945. The article examines the state of relations between the two countries after the breakup of the Soviet Union and in the years 2000-2010, after the rise to power in Russia of Vladimir Putin. Although the two parties have committed in April 2010 to re-discuss the dispute, the possibility that the peace treaty is signed in the near future are slim.